2011
DOI: 10.1143/jjap.50.098001
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray Conversion Efficiencies in Laser-Produced Xenon and Tin Plasmas in a 5–17 nm Wavelength Range

Abstract: Soft X-ray conversion efficiencies in a 5–17 nm wavelength range in xenon and tin plasmas produced by a 1.06 µm Q-switched neodymium-doped yttrium aluminum garnet laser were investigated. They were measured to be 25 and 20% for the xenon and tin plasmas, respectively at a laser intensity of about 2×1010 W/cm2. These results indicate that a stand-alone soft X-ray source using a laser-produced xenon or tin plasma is useful for various applications that require intense, soft X-ray photons in a wide wavelength ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Using the Thomson parabola spectrometer, we determined the average charge number of ions Z to be 2 in the rotating drum target at a laser intensity of about 10 10 W cm −2 [14]. It would be explained physically by a possible increase in the surface temperature of the target layer caused by the two wipers in the rotating drum, which would form a dense xenon gas layer on the surface of the cryogenic target [11]. Such a gas layer would work as a thin buffer gas layer that not only mitigates but also recombines the fast ion debris emitted from an inner highdensity plasma region with cold electrons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Thomson parabola spectrometer, we determined the average charge number of ions Z to be 2 in the rotating drum target at a laser intensity of about 10 10 W cm −2 [14]. It would be explained physically by a possible increase in the surface temperature of the target layer caused by the two wipers in the rotating drum, which would form a dense xenon gas layer on the surface of the cryogenic target [11]. Such a gas layer would work as a thin buffer gas layer that not only mitigates but also recombines the fast ion debris emitted from an inner highdensity plasma region with cold electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Soft x-ray emission spectra in a wide wavelength range of 5-17 nm [11] were observed by a transmission grating spectrometer [12,13] in order to obtain the x-ray conversion efficiency (CE). Although soft x-rays in this wide wavelength range are useful for a variety of applications, we measured as a reference only the energy transmission of soft x-rays at 13.5 nm [3] through the buffer gas as a function of the gas density.…”
Section: Methodsmentioning
confidence: 99%
“…2. 4 In separate experiments, we found that the angular distribution in 2π space for the EUV (13.5 nm ± 1% bandwidth) emission was E 0 (cos φ 1 ) 0.38 , where E 0 and φ 1 were the soft X-ray energy flux per unit solid angle and the angle from the target normal, 6 respectively. We assumed the same angular distribution for the 5-17-nm soft X-rays and EUV emission and estimated the total soft X-ray energy in the 2π space.…”
Section: Soft X-ray Sourcementioning
confidence: 87%
“…On the other hand, we found that the xenon plasma could be a highly efficient light source owing to its broadband, but intense soft X-ray emissions. 4 This characteristic is useful for the application of xenon plasma in material photo processing technologies, which require broadband absorption (i.e., photoreactions) instead of narrowband-selective absorptions. Matsuo et al found that laser plasma soft X-ray irradiation before excimer laser annealing (ELA) reduced the critical energy density for the initiation of crystallisation of amorphous silicon films.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The LPX system is compact in size compared with a synchrotron radiation facility. 14,15) It is expected to use in industry for solar cells. It is found that the crystallization temperature of an a-Si film on a glass substrate was reduced from 680 to 580 C by soft X-ray irradiation.…”
mentioning
confidence: 99%